2013
DOI: 10.1136/bmjopen-2013-003493
|View full text |Cite
|
Sign up to set email alerts
|

Strategies TO reduce time delays in patients with AcuTe coronary heart disease treated with primary PCI—the STOP WATCH study: a multistage action research project

Abstract: ObjectiveTo identify, evaluate and reduce system delay times in an ST-elevation myocardial infarction (STEMI) network by targeted reorganisation of logistics and personal feedback to staff on time delays.DesignMultistage action research project. Three study phases were used (exploration, tailored intervention and evaluation).SettingSingle centre study, Sweden.PatientsConsecutive patients (N=156) with prehospital STEMI onset treated with primary percutaneous coronary intervention (PCI).InterventionsAreas of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Sixteen studies reported on paramedic actions for trauma, stroke and MI patients that were in addition to standard handover [ 24 – 39 ]. They did not directly provide patient care, and the paramedic role was restricted to prehospital activation [ 25 , 37 ] or transportation of patients to condition-specific specialist facilities such as catheterisation laboratory for MI patients [ 26 , 28 , 30 33 , 38 ], radiology for acute stroke patients [ 24 , 27 , 34 , 36 , 39 ], radiology for trauma (hip fracture) patients [ 35 ], or a pacing centre for patients with complete heart block [ 29 ]. In one study paramedics were also responsible for delivery of blood test results of trauma (hip fracture) patients to the hospital laboratory [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies reported on paramedic actions for trauma, stroke and MI patients that were in addition to standard handover [ 24 – 39 ]. They did not directly provide patient care, and the paramedic role was restricted to prehospital activation [ 25 , 37 ] or transportation of patients to condition-specific specialist facilities such as catheterisation laboratory for MI patients [ 26 , 28 , 30 33 , 38 ], radiology for acute stroke patients [ 24 , 27 , 34 , 36 , 39 ], radiology for trauma (hip fracture) patients [ 35 ], or a pacing centre for patients with complete heart block [ 29 ]. In one study paramedics were also responsible for delivery of blood test results of trauma (hip fracture) patients to the hospital laboratory [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with metropolitan Italian data, EMS bypassing the emergency department and early triage based on electrocardiogram can significantly reduce system delays. When EMS bypasses the high proportion of emergency visits, reducing decision time alone can lead to further reduced system delays [ 27 ]. With the publicity and popularization of acute myocardial infarction-related knowledge, at this stage, with citizens having a greater understanding of the discriminatory symptoms of acute myocardial infarction, the focus should be on promoting awareness of the EMS treatment process and its benefits and on reducing total myocardial ischemia time, and improve the prognosis for patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…There are several suggestive measures to reduce the door-to-door time and centers should choose one or more based on local considerations. Some of these strategies require investment in infrastructure such as providing prehospital ECGs, while some others can be applied in most hospitals, with limited budgets, by modifying the internal protocols such as the activation of the STEMI code by emergency physicians and the direct transfer of patients to the cath lab, bypassing the ER [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%